2022
DOI: 10.1021/acsanm.2c04177
|View full text |Cite
|
Sign up to set email alerts
|

Computational Study on the Regulatory Mechanism of Cell Membrane Wrapping on Liposomes by Embedded Bowl-like Nanostructures for Drug Delivery

Abstract: Controlling the nanoparticle's (NP) ability to facilitate cell uptake is particularly desirable for biomedical applications, such as drug delivery. Despite growing evidence highlighting the pivotal role of mechanical properties in biological performances of NPs, consensus regarding how stiffness regulates the cell entry of NPs is lacking. Here, we design and elucidate cell membrane wrapping on soft liposomes in which rigid bowl-like nanostructures are embedded. Compared with pure liposomes, which are often par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…Studies have shown that the cellular uptake efficiency of positively charged nanoliposomes was affected by their rigidity when they are taken up by cells through endocytosis. , Therefore, DPPC nanoliposomes might be taken up by Caco-2 cells through endocytosis. Soft nanoliposomes are believed to have a low endocytosis efficiency because they are effortless to deform during endocytosis. , This increases the contact area between the nanoliposome and the cell membrane, requiring the cell membrane to increase the energy to engulf the liposome and a greater adhesion to complete the encapsulation of the membrane. , Endocytosis of soft liposomes is also hindered by uneven ligand distribution . The same situation was found by Dai et al, where the most rigid liposome (Lip 4) showed the greatest degree of cellular uptake.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Studies have shown that the cellular uptake efficiency of positively charged nanoliposomes was affected by their rigidity when they are taken up by cells through endocytosis. , Therefore, DPPC nanoliposomes might be taken up by Caco-2 cells through endocytosis. Soft nanoliposomes are believed to have a low endocytosis efficiency because they are effortless to deform during endocytosis. , This increases the contact area between the nanoliposome and the cell membrane, requiring the cell membrane to increase the energy to engulf the liposome and a greater adhesion to complete the encapsulation of the membrane. , Endocytosis of soft liposomes is also hindered by uneven ligand distribution . The same situation was found by Dai et al, where the most rigid liposome (Lip 4) showed the greatest degree of cellular uptake.…”
Section: Discussionmentioning
confidence: 78%
“…Soft nanoliposomes are believed to have a low endocytosis efficiency because they are effortless to deform during endocytosis. 36,63 This increases the contact area between the nanoliposome and the cell membrane, requiring the cell membrane to increase the energy to engulf the liposome and a greater adhesion to complete the encapsulation of the membrane. 15,64 Endocytosis of soft liposomes is also hindered by uneven ligand distribution.…”
Section: Discussionmentioning
confidence: 99%
“…[ 141–143 ] Typically, the anisotropic structure of BNPs promotes endocytosis by cancer cells, proved by either experimental or computational studies. [ 144,145 ] For instance, Wu et al. [ 141 ] prepared ruthenium (Ru) containing BNPs self‐assembled from a novel Ru containing triblock copolymer, acting as a photoactivated polymetallodrug for combined photodynamic therapy and photochemotherapy in vivo, as shown in Figure .…”
Section: Emerging Applications Of Bnpsmentioning
confidence: 99%
“…Polymer self-assembly has been widely used to prepare a large variety of nanomaterials, including micelles, vesicles, cylinders, and lamellaes, showing significant potentials in drug delivery, antimicrobial, anticancer and catalysis, etc. Among them, bowl-shaped nanoparticles (BNPs) have drawn wide attention due to their anisotropic structure and a large opening on the surface, promoting their applications in smart carrier especially for large-sized cargoes, cancer therapy, water remediation, and nanomotors . The recent advances of polymeric BNPs have been summarized in our recent review article .…”
Section: Introductionmentioning
confidence: 99%